Alcohol and cancer: an overview with special emphasis on the role of acetaldehyde and cytochrome P450 2E1 - Seitz, Helmut K.; Mueller, Sebastian (Biological basis of alcohol-induced cancer, 2015)
The mechanisms by which chronic alcohol consumption enhances carcinogenesis include acetaldehyde (AA) generated by alcohol dehydrogenase and reactive oxygen species (ROS) generated predominantly by cytochrome P450 2E1 (CYP2E1), but also by other factors during inflammation. In addition, ethanol also alters epigenetics by changing DNA and histone methylation and acetylation. A loss of retinoic acid due to a CYP2E1-related enhanced degradation results in enhanced cellular proliferation and decreased cell differentiation. Changes in cancer genes and in signaling pathways (MAPK, RAS, Rb, TGFβ, p53, PTEN, ECM, osteopontin, Wnt) may also contribute to ethanol-mediated mechanisms in carcinogenesis. Finally, immunosuppression may facilitate tumor spread. In the present review major emphasis is led on AA and ROS. While AA binds to proteins and DNA generating carcinogenic DNA adducts and inhibiting DNA repair and DNA methylation, ROS results in lipid peroxidation with the generation of lipid peroxidation products such as 4-hydoxynonenal which binds to DNA-forming highly carcinogenic exocyclic DNA adducts. ROS production correlates significantly with CYP2E1 in the liver but also in the esophagus, and its generation can be significantly reduced by the specific CYP2E1 inhibitor clomethiazole. Finally, CMZ also inhibits alcohol-mediated nitrosamine-induced hepatocarcinogenesis.